2023
DOI: 10.1021/acs.biochem.3c00109
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Inactivation of SARS-CoV-2 by Lectin Engagement with Two Glycan Clusters on the Spike Protein

Abstract: Host cell infection by SARS-CoV-2, similar to that by HIV-1, is driven by a conformationally metastable and highly glycosylated surface entry protein complex, and infection by these viruses has been shown to be inhibited by the mannose-specific lectins cyanovirin-N (CV-N) and griffithsin (GRFT). We discovered in this study that CV-N not only inhibits SARS-CoV-2 infection but also leads to irreversibly inactivated pseudovirus particles. The irreversibility effect was revealed by the observation that pseudovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…S17). Interestingly, site-directed mutagenesis demonstrated that the N657Q/D point mutation increased infectivity for reasons not yet clarified (Nangarlia et al, 2023; Yang et al, 2022). Visual inspection and H-bond analysis show that the N657 glycan gains interactions with D843 solely upon ACE2 binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S17). Interestingly, site-directed mutagenesis demonstrated that the N657Q/D point mutation increased infectivity for reasons not yet clarified (Nangarlia et al, 2023; Yang et al, 2022). Visual inspection and H-bond analysis show that the N657 glycan gains interactions with D843 solely upon ACE2 binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B, Fig. S10, 12,13). Similarly, in the third intermediate state, the longer dissociation time in the presence of GAGs is due to stronger interactions established between the ACE2 N90 glycan and the spike RBDs, which result in a narrower crevice where the N-glycan is inserted (Fig.…”
Section: N-glycans Of Spike and Ace2 Concur With Highly Sulfated Gags...mentioning
confidence: 94%
See 2 more Smart Citations
“…There are already prophylactic strategies against other viruses that leverage binding to glycans on the viral spike protein: several anti-HIV antibodies bind to the glycan shield rather than amino acid epitopes, and other globular-lectin-protein-based inhibitors such as griffithsin exhibit broad inhibitory activity against a variety of viruses [ 54 , 111 , 112 , 113 ]. Recent literature has shown considerable success when griffithsin treatment was combined with a therapeutic that targeted a different epitope on the SARS-CoV-2 spike—a designed viral fusion inhibitor called EK1, sulfated polysaccharides called carrageenan, or another glycan-binding inhibitor called cyanovirin [ 114 , 115 , 116 , 117 ]. These results hint that if new inhibitors could be designed against unique SARS-CoV-2 epitopes (such as the N17/61/74 or N122/145/234 glycan clusters), they could be combined with other existing COVID-19 therapeutics to create a more potent prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%